Communication about science in a traditional museum: visitors’ and staff’s perceptions - Rennie, Leonie; Williams, Gina (2006)
This study investigated visitors’ and staff’s perceptions about the communication of science in a traditional natural history museum. The research examined the science-related outcomes for adult visitors and explored visitors’ and staff’s ideas of science and how it is portrayed at the museum. Data were collected by questionnaire and interview from 84 staff and 102 visitors. Both groups held positive views about science, its importance and the need for everyone to understand it. Comparison of visitors’ pretest and posttest scores on the questionnaire revealed some significant changes, several suggesting a change to views about science that were less “scientific.” Most visitors thought that their ideas about science had not changed as a result of their visit, but they were positive about the museum as a place for learning science. Staff held more “scientific” views about the nature of science than did visitors; they recognized the potential of the museum to educate people about science, but felt it needed to be presented as more relevant and accessible, particularly in terms of science as a cultural practice. Neither staff nor visitors perceived that the museum stimulated visitors to think critically about science. While acknowledging that interpreting complex scientific knowledge into exhibits readily understood by lay visitors and displaying controversy are difficult, these challenges must be addressed if visitors are to be encouraged to think about science and the social, cultural and political contexts which shape it.